2017
DOI: 10.1111/jpn.12781
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics intake from proximal or distal gastrointestinal tract: The investigation on intestinal morphology and performance of Japanese quail

Abstract: SummaryThe aim of the present study was to investigate the efficacy of early single-dose probiotics administered from proximal or distal gastrointestinal tract on quails' performance and small intestinal morphology. A total of 120 Japanese quail (Coturnix coturnix japonica) 1-d-old chicks were divided into the following experimental groups before being transferred to the raising room: (i) control (no probiotic administered); (ii) oral group (received probiotics via oesophageal gavage); and (iii) vent lip group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…On the other hand, ileum crypt depth was significantly lower in ANT and probiotic groups compared with the CON treatment ( p < 0.05). Similar results with this research were observed by other researchers (Salim et al, ; Seifi, Karimi‐Torshizi, & Deldar, ). Consistent to the present observation, Sen et al () reported that supplementation of probiotic in broiler feeds increased villus height, villus height crypt depth ratio, goblet cell numbers and decreased depth of crypt as compared with those fed CON diets.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, ileum crypt depth was significantly lower in ANT and probiotic groups compared with the CON treatment ( p < 0.05). Similar results with this research were observed by other researchers (Salim et al, ; Seifi, Karimi‐Torshizi, & Deldar, ). Consistent to the present observation, Sen et al () reported that supplementation of probiotic in broiler feeds increased villus height, villus height crypt depth ratio, goblet cell numbers and decreased depth of crypt as compared with those fed CON diets.…”
Section: Discussionsupporting
confidence: 93%
“…Secretory IgA promotes the clearance of antigens and pathogenic bacteria from the lumen by blocking their access to epithelial receptors, entrapping them in mucus, and facilitating their removal by peristaltic and mucociliary activities [37]. Beneficial bacteria can also increase mucin synthesis and the number of goblet cells (GC) in the intestinal epithelium [38]. Mucins (produced by GC) are large glycoproteins that cover the epithelial surfaces of the intestine and form a mucus layer to protect IEC from gut health challenges [39].…”
Section: The Role Of Probiotics On the Control Of Inflammationmentioning
confidence: 99%
“…We calculated the chicken villus surface area using the formula, [πdh + π (d/2) 2 ] (Ferrer, Planas, & Moretó, 1995;Seifi, Karimi-Torshizi, & Deldar, 2018). We calculated the chicken villus surface area using the formula, [πdh + π (d/2) 2 ] (Ferrer, Planas, & Moretó, 1995;Seifi, Karimi-Torshizi, & Deldar, 2018).…”
Section: Intestinal and Villus Growthmentioning
confidence: 99%
“…The villus height (h) was measured from the villus tip to the bottom, and the average width (d) was calculated from widths of the tip, middle and bottom (B) of the villus. We calculated the chicken villus surface area using the formula, [πdh + π (d/2) 2 ] (Ferrer, Planas, & Moretó, 1995;Seifi, Karimi-Torshizi, & Deldar, 2018). In the formula, the longest (a) and shortest (b) diameter of the jejunal section were used to calculate the average inner diameter (a + b)/2 and the perim-…”
Section: Intestinal and Villus Growthmentioning
confidence: 99%